All aspects of galactosemia: a single center experience - Akgun, Abdurrahman; Dogan, Yasar (Walter de Gruyter Gmbh, 2023)
Objectives: Classic galactosemia is a galactose metabolism disorder due to galactose-1-phosphate uridyltransferase deficiency. In this study we report the clinical features of a cohort of children with classic galactosemia.Methods: A retrospective evaluation was made of the files of 42 cases followed up for a diagnosis of classic galactosemia between January 2000 and December 2021. The data were collected of clinical, laboratory and genetic characteristics.Results: The cases comprised of 25 (59.5%) girls and 17 (40.5%) boys with a median age of 15 days (range, 1 day to 9 years) at diagnosis. In addition, thirty-six cases (92.3%) could be diagnosed before they were 4 months old by hospitalization with various clinical findings, primarily liver dysfunction. The most common complaints on presentation were jaundice (78.4%) and vomiting (27%) and the most frequently seen genetic pathogenic variant was c.563A > G (p.Gln188Arg) (92.4%).Conclusions: It can be emphasized that there is a need for a neonatal screening program for classic galactosemia to be able to increase the possibility of early diagnosis and to be able to start treatment before the development of a severe clinical picture.
Keywords: cataract; classic galactosemia; jaundice